Rozwój człowieka – rozwój świata – refleksja w rocznicę wielkich papieskich encyklik społecznych - Stępniak, ks. Marek (Annales. Etyka w Życiu Gospodarczym, 2008)
The problem of the development of a human person and the whole mankind has a significant place in the post Vaticanum Secundum social teaching of the Catholic church. This year’s anniversary of two social encyclicals: Paul VI’s Populorum progressio (1967) and John Paul II’s Sollicitudo rei socialis (1987) indicates the need of undertaking theological and anthropological reflection upon the process of development. The Catholic social teaching placing a human person in the center of all social, political and economic processes evaluates the quality of development from the perspective of respecting human dignity and rights. Although the development issues have originated from social teaching of local churches of Africa and Latin America, thanks to the social encyclicals it took on a global dimension. The social teaching of the Catholic church by indicating the need of the integral development of a human person and the whole mankind, points out the problems of material, spiritual poverty and violation of human rights. Therefore, the teaching about development is an integral element of the preferential option for the poor in the ministry of the Catholic church.